Sequence Variation in DDAH1 and DDAH2 Genes Is Strongly and Additively Associated with Serum ADMA Concentrations in Individuals with Type 2 Diabetes - Abhary, Sotoodeh (Public Library of Science, 2010)
BACKGROUND: Asymmetric dimethylarginine (ADMA), present in human serum, is an endogenous inhibitor of nitric oxide synthase and contributes to vascular disease. Dimethylarginine dimethylaminohydrolase (DDAH) is an ADMA degrading enzyme that has two isoforms: DDAHI and DDAHII. We sought to determine whether serum ADMA levels in type 2 diabetes are influenced by common polymorphisms in the DDAH1 and DDAH2 genes. METHODOLOGY/PRINCIPAL FINDINGS: Relevant clinical parameters were measured and peripheral whole blood obtained for serum and genetic analysis on 343 participants with type 2 diabetes. Serum ADMA concentrations were determined by mass spectroscopy. Twenty six tag SNPs in the DDAH1 and 10 in the DDAH2 gene were genotyped in all subjects and tested for association with serum ADMA levels. Several SNPs and haplotypes in the DDAH genes were strongly associated with ADMA levels. Most significantly in the DDAH1 gene, rs669173 (p = 2.96×10(−7)), rs7521189 (p = 6.40×10(−7)), rs2474123 (p = 0.00082) and rs13373844 (p = 0.00027), and in the DDAH2 gene, rs3131383 (p = 0.0029) and the TGCCCAGGAG haplotype (p = 0.0012) were significantly associated with ADMA levels. Sub-analysis by diabetic retinopathy (DR) status revealed these variants were associated with ADMA levels predominantly in participants without DR. Combined analysis of the most strongly associated SNPs in DDAH1 (rs669173) and DDAH2 (rs3131383) revealed an additive effect (p = 1.37×10(−8)) on ADMA levels. CONCLUSIONS/SIGNIFICANCE: Genetic variation in the DDAH1 and 2 genes is significantly associated with serum ADMA levels. Further studies are required to determine the pathophysiological significance of elevated serum ADMA in type 2 diabetes and to better understand how DDAH gene variation influences ADMA levels.